2021
DOI: 10.1097/mpg.0000000000003148
|View full text |Cite
|
Sign up to set email alerts
|

Transition Services for Paediatric Inflammatory Bowel Disease

Abstract: Objectives: Patients with paediatric inflammatory bowel disease (IBD) constitute one of the largest cohorts requiring transition from paediatric to adult services. Standardised transition care improves short and long-term patient outcomes. This study aimed to detail the current state of transition services for IBD in the United Kingdom (UK). Methods: We performed a nationwide study to ascertain current practice, facilities and resources for children and young people with IBD. Specialist paediatric IBD centres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…Disease severity did not affect HME rates. These studies highlight areas to address in transition of care, and add to the data from Ashton et al (6) who reported gaps and opportunities in transition services for children with IBD in a multicenter study from the United Kingdom.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 56%
“…Disease severity did not affect HME rates. These studies highlight areas to address in transition of care, and add to the data from Ashton et al (6) who reported gaps and opportunities in transition services for children with IBD in a multicenter study from the United Kingdom.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 56%
“…Twenty-one paediatric gastroenterology centres were identified across England, Wales, Scotland and Northern Ireland representing specialist centres for PIBD as previously described 13. An electronic survey was used to report experience.…”
Section: Methodsmentioning
confidence: 99%
“…The response highlights the lack of formal transition services when the condition is rare. Extrapolation of this observation to other paediatric conditions indicates that many children will not have a structured transition process, something which has been associated with poorer outcomes in conditions such as IBD (2). The need for IBD transition guidelines is clear, however we also acknowledge the need to account for local factors such as patient background, disease prevalence and geographic distribution of adult hospitals.…”
mentioning
confidence: 93%
“…R eply: We read with interest the response by Yang et al (1,2) to our article on transition services for paediatric inflammatory bowel disease (IBD) in United Kingdom. The response highlights the lack of formal transition services when the condition is rare.…”
mentioning
confidence: 99%